2009
DOI: 10.1080/15287390902959672
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Potassium Iodide (KI) and Ammonium Perchlorate (NH 4 ClO 4 ) to Ameliorate 131 I - Exposure in the Rat

Abstract: Nuclear reactor accidents and the threat of nuclear terrorism have heightened the concern for adverse health risks associated with radiation poisoning. Potassium iodide (KI) is the only pharmaceutical intervention that is currently approved by the Food and Drug Administration for treating (131)I(-) exposure, a common radioactive fission product. Though effective, KI administration needs to occur prior to or as soon as possible (within a few hours) after radioactive exposure to maximize the radioprotective bene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…We evaluated the efficacy of these post-exposure treatments by monitoring 131 I − in the thyroid gland, urine, and serum for up to 3 days after dosing. This study design was based on a previous study in our laboratory [15], which showed that at 15 hours after treatment with KI or NH 4 ClO 4 , the perchlorate treated rats excreted three times the amount of 131 I − in urine compared with control treatments, while stable iodide treated rats excreted only twice the amount of 131 I − in urine compared with control treatments. In the current study, we confirm our earlier results that perchlorate treatment led to faster 131 I − excretion compared with KI treatment (Table 2).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We evaluated the efficacy of these post-exposure treatments by monitoring 131 I − in the thyroid gland, urine, and serum for up to 3 days after dosing. This study design was based on a previous study in our laboratory [15], which showed that at 15 hours after treatment with KI or NH 4 ClO 4 , the perchlorate treated rats excreted three times the amount of 131 I − in urine compared with control treatments, while stable iodide treated rats excreted only twice the amount of 131 I − in urine compared with control treatments. In the current study, we confirm our earlier results that perchlorate treatment led to faster 131 I − excretion compared with KI treatment (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…In previous rat studies we reported that over a 15 hour post dosing period, KI and NH 4 ClO 4 were equally effective at reducing thyroid gland exposure to 131 I − [15]. However, NH 4 ClO 4 was more effective at increasing urinary clearance of 131 I − than KI.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…An alternative could be perchlorate (Harris et al 2009 ). The NI-symporter is not selective for iodide, but transports several related monovalent anions.…”
Section: Introductionmentioning
confidence: 99%